Selective Estrogen Receptor Modulator-Like Activities of Herba epimedii Extract and its Interactions With Tamoxifen and Raloxifene in Bone Cells and Tissues - Zhou, Liping; Wong, Ka-Ying; Yu, Wenxuan; Poon, Christina Chui-Wa; Xiao, Huihui; Chan, Chi-On; Mok, Daniel Kam-Wah; Zhang, Yan; Wong, Man-Sau (Frontiers in Pharmacology, 2021)
Herba Epimedii (HEP), a kidney-tonifying herb, has been commonly used alone or in formula for strengthening kidney function and treating bone disorders. Its bone protective activity has been demonstrated to be via estrogen receptor (ERs). HEP activates the phosphorylation of ERα in an estrogen response element (ERE)-dependent manner. We examined the bone protective effects ofHEP and its potential interactions with Selective Estrogen Receptor Modulators (SERMs, such as tamoxifen and raloxifene) as they act via the same ERs. Six-month-old mature Sprague Dawley sham-operated (Sham) or ovariectomized (OVX) rats were treated with either vehicle, 17ß-estradiol (1.0 mg/kg.day), tamoxifen (Tamo, 1.0 mg/kg.day), raloxifene (Ralo, 3.0 mg/kg.day), HEP (0.16 g/kg.day) or its combinations with respective SERMs (HEP+Tamo; HEP+Ralo) for 12 weeks. HEP, SERMs, as well as their combinations significantly restored changes in bone mineral density (BMD), trabecular bone properties and bone turnover biomarkers induced by ovarian sex hormone deficiency in ovariectomized rats. Besides the increase in serum estradiol, inhibition onfollicle stimulating hormone (FSH) might also be involved in the osteoprotective activities of HEP and SERMs. HEP interacted with SERMs to protect bones from ovarian sex hormone deficiency without altering their bone protective activities. HEP neither induced changes in uterus weight nor altered the uterotrophic activity of SERMs in OVX rats. In human osteosarcoma MG-63 cells, HEP-treated serum (HEP-Ts) significantly promoted alkaline phosphatase (ALP) activity like the crude HEP extract did but did not stimulate estrogen response element (ERE) activity. Our studyalso reported that biologically activated HEP interacted with SERMs to promote ALP activity without altering the action of SERMs at most of the concentrations tested in MG-63 cells. HEP exerted bone protective activity and the use of HEP did not alter the bone protective activities of SERMs when they were used simultaneously in an estrogen-deficient rat model.